SYSTEMATIC LITERATURE RIVIEW: DESAIN LKPD BERBANTUAN GEOGEBRA MENGGUNAKAN PENDEKATAN PMRI TERHADAP KEMAMPUAN PEMAHAMAN KONSEP - Dea Suniar, Akhyumita; Luthfiana , Maria; Refianti, Rani (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2025)
A deep understanding of mathematical concepts is very important so that students can associate the subject matter with real life and be able to think critically in solving problems. However, the reality is that many students have difficulty in understanding concepts because of the conventional learning approach. In the digital era, interactive, visual, and contextual learning media are needed such as LKPD assisted by Geogebra with the PMRI approach. This study aims to examine various studies on the design of LKPD assisted by Geogebra with the PMRI approach and its impact on students' understanding of mathematical concepts. The method used is Systematic Literature Review (SLR) with stages 1) Research Question; 2) Selection Criteria; 3) Search Strategy; 4) Select Studies; 5) The Quality Of Studiest; 6) Synthesis Result. Literature sources are obtained from databases such as Google Scholar, SINTA, and Garuda with the keywords LKPD, Geogebra, PMRI and understanding concepts in the period of 2020–2025. The results of the study show that the use of Geogebra-assisted LKPD using the PMRI approach is able to increase students' active involvement, high-level thinking skills, especially in improving students' understanding of mathematical concepts.